Economic impact of climate change on farmers' income in Ramanathapuram district: A ricardian analysis - K PRAVEENA; A MALAISAMY; ANBUKANI P; K PRABAKARAN; S PADMA RANI; R BALAJI (The Indian Journal of Agricultural Sciences)
Climate change presents a growing challenge to agriculture, particularly in drought-prone regions like Ramanathapuram district, Tamil Nadu, where farming remains a primary livelihood. The present study was carried out from January to June 2024 in Ramanathapuram district, Tamil Nadu, focusing on analyzing the effects of climate change on farmers' livelihoods. This study employs the Ricardian model to assess the long-term impact of climate variability on farm income and employment, utilizing climate data from 1994 to 2023 and survey responses from 120 randomly selected farmers. Findings indicate a 1.3°C rise in maximum temperature and a 22% decline in rainfall over the study period, contributing to a 38% reduction in crop yields, with paddy, pulses, and millet being the most affected. The Ricardian analysis revealed that a 1% increase in maximum temperature during the rainy (kharif) season reduces net farm income by 0.45%, while a 1% rise in rainfall enhances income by 0.23%. Farmers identified drought (91.7%), groundwater depletion (82%), and soil degradation (65%) as major climate-induced challenges. Additionally, agricultural labour demand declined by 25%, prompting many farmers to shift to non-agricultural employment. Despite the critical role of agriculture in rural livelihoods, limited research has focused on quantifying the economic implications of climate change in Tamil Nadu’s coastal districts. This study bridges this gap by providing empirical evidence on climate-induced income and employment shifts, emphasizing the need for climate-resilient policies and sustainable agricultural strategies to ensure long-term economic stability.